Razón, intuición y experiencia de la vida. Coincidencias y divergencias entre H. Bergson y J. Ortega y Gasset - Atencia, J. M.ª (Logos. Anales del Seminario de Metafísica, 2003)
In this paper a comparison of some central elements of the philosophies of H.Bergson and J. Ortega and Gasset is tried. After analyzing their coincidences and divergences we will establish their common ownership to a line of development of the european metaphysics that starts up from the critic to the kantismo.